Modern Solutions to Prevent the Risk of Perinatal Premature Birth - Shavazi Nargiz Nuralievna; Rayimjanova Nazokat Farxodovna (Journal of Science in Medicine and Life, 2024)
Risk groups during pregnancy - this concept in medicine is necessary to minimize the possibility of complications that can lead to premature birth, congenital pathologies or fetal death during pregnancy. There are groups to detect pregnancy that require the supervision of special specialists. But this does not mean that the future mother will have health problems. It's just that a woman who is in the risk group for some reason has a number of pathological symptoms, the development of which leads to premature birth of a child, delayed fetal development, asphyxia (suffocation), etc. Therefore, he needs some procedures and medical interventions.